Lacticaseibacillus rhamnosus LRa05 in the treatment of acute diarrhea in children: a randomized controlled trial - Chen, Ke; Zeng, Kaihong; Jin, Shanshan; Ma, Yu; Cai, Limei; Xu, Ping; Nie, Yang; Luo, Li; Yu, Qinghua; Liu, Changqi (Frontiers in Nutrition, 2024)
Introduction The goal of this study is to assess the efficacy and safety of Lacticaseibacillus rhamnosus LRa05, as an adjunct to the treatment of acute watery diarrhea in children. Methods Eligible diarrheal children were randomized into intervention group (IG, n = 57) and control group (CG, n = 54), and given probiotics or placebo, respectively. Results The total duration of diarrhea in the IG (121.4 ± 13.7 h) was significantly shorter than that in the CG (143.9 ± 19.8 h, p < 0.001). More children in the IG showed improvements in diarrhea than those in the CG for both per protocol analysis (70.2 vs. 46.3%, p = 0.01) and intention-to-treat analysis (66.7 vs. 41.7%, p = 0.003). The LL-37 levels in the IG was markedly higher than that in the CG after the intervention (4349.35 ± 1143.86 pg./g vs. 3682.49 ± 869.21 pg./g, p = 0.039). The intervention led to higher abundance of Bifidobacterium longum and lower abundance of Enterococcus faecium, Lactobacillus rhamnosus, and Bacteroides fragilis (p < 0.05). LRa05 treatment upregulated the functional genes of gut microbiota involving immunity regulation. Discussion Administration of the Lacticaseibacillus rhamnosus LRa05 at a dose of 5 × 109 CFU/day to children aged 0-3 years resulted in shorter duration of diarrhea, faster improvement in fecal consistency, and beneficial changes in gut microbiome composition and gene functions. Clinical trial registration The present study has been approved and registered in the Chinese Clinical Trial Registration Center with the registration number of ChiCTR2100053700 (https://www.chictr.org.cn/showproj.html?proj=141082).